mindclaw
Rank #23233 on Subscribers
Level 239 Comments: Ambassador Of Lulz Offline
Send mail to mindclaw Block mindclaw Invite mindclaw to be your friend Last status update:  

 
Date Signed Up:  11/03/2012 
Last Login:  12/08/2016 
Stats  
Content Thumbs:  1998 total, 2716 , 718 
Comment Thumbs:  5056 total, 5237 , 181 
Content Level Progress:  98% (98/100) Level 119 Content: Funny Junkie → Level 120 Content: Respected Member Of Famiry 
Comment Level Progress:  33% (33/100) Level 239 Comments: Ambassador Of Lulz → Level 240 Comments: Doinitrite 
Subscribers:  3 
Content Views:  144812 
Total Comments Made:  317 
FJ Points:  5956 
Abuse it
www.pixiv.net/member_illust.php?mode=medium&illust_id=53870703
thats weird though
like someone just changed how maths works
It gives me the answer of 9.
(Which is incorrect)
As far as I know every calculator should give the wrong answer of 9.
Yours is magical like I can't explain why yours gives the right answer..
It'll always say 9
and the programming has it go left to right with multiplication and division so it you divide by 2 first
it treats it like a seperate term shit doesnt work
You'd imagine that with the modern technology that they'd be able to fix such an error.
People rely too heavily on calculators.
a(b+c) = a*(b+c)
=> a : b(c+d) = a : b * (c+d) != a : (b * (c+d)
second problem: division
a : b * c = (a:b)*c != a : (b*c) = a : b : c
a  b + c = (ab)+c != a  (b+c) = a  b  c
this makes
6 : 2(1+2) = 6 : 2 * 3 = (6:2) * 3 = 3 * 3 = 9
Unfortunately I'm too lazy to show the higher math behind it (easy in german, hard in non native language) but if someone is interested just search for "Multiplicative Inverse Axiom"
so you have to multiply before you divide
you treat the parentheses as a variable before you know the result of them
because coefficients work the same way for both
6/2x =/= 3x
its 3x^1
so you wouldnt get 9
if you put x back in with 3x^1 then that's 3/3 = 1
the order of operations means you work out parentheses first and coefficients are the same term as the parentheses
so again
you multiply first
8 : 2 * 2 is 8 not 2.
2x is the same thing as 2*x but in the same term
which also applies for coefficients
and i didnt write 8 anywhere
I took another example with 8 : 2 * 2 = 8 to show this. Using your argumentation we would have 8 / (2 * 2) = 2 which is wrong. There is something called left associative operation which is the standard way of interpretation if not stated otherwise. The problem here is that the way you used might not be wrong in terms of mathematical theorems but it is in mathematical associative axioms.
b(c+d) == (b* (c+d))
ignore the other one
b(c+d) == (b* (c+d))
And again, this isn't stated in the original term. It states:
6 : 2(1+2)=?
a : b(c+d) = a : b * (c+d) = ?
a : b * e = ?
This is what you have to do using the left associative operation  which you have to do unless stated otherwise (using brakets).
Yours would have been stated as
6 : (2(1+2))=?
it doesnt say 2*(1+2) it says 2(1+2)
and likewise its not b*e its be
The thing is, that your operator states that a*(b+c) != a(b+c)
The definition of a coefficient alway has the word multiplication in it and doesn't differ from the form a*x = ax.
more like algebraic notation
a coefficient is different to just multiplying because of the order
coefficients always come first
The Multiplicative Inverse Axiom states that the product of a real number and its multiplicative inverse is 1. Every real number has a unique multiplicative inverse. The reciprocal of a nonzero number is the multiplicative inverse of that number. Reciprocal of x is 1/x. x * 1/x = 1. x * x´ = 1 for x´ = 1/x
Typical notations for x´ are x^1 or 1/x. The division is defined as multiplication with the inverse of the divisor. So a : b * c = a * b^1 * c != a * b^1 * c^1 = a : b : c = a : (b:c).
And for us 6 : 2 * (1 + 2) = 6 : 2 * 3 = 6 * 2^1 * 3= 6 * 1/2 * 3 = 9
when they are
its not 6 * 2^1 * (2+1) its 6 * (2(1+2))^1